DENTAL AND ORAL HEALTH COUNSELING AND EXAMINATION AT SDN PAMONGAN 1 MOJO, KEDIRI - lutfi, erik irham; Brahmbhatt, Shrutt; Vitasmoro, Pamadya; Santoso, Ariadi (Universitas Kadiri, 2024)
Dental and oral health problems remain a major concern in Indonesia, particularly among primary school children, with dental caries being the most prevalent issue. This community service activity was conducted through collaboration between Universitas Kadiri (Indonesia), Karnavati University (India), and SDN Pamongan 1 Mojo Kediri. The aim was to screen students’ dental and oral health while providing counseling on proper oral hygiene practices. The method included three stages: an opening session, dental examinations using disposable diagnostic instruments, and counseling sessions emphasizing correct brushing techniques, diet control, and regular check-ups. A total of 86 students participated, with results showing 74% had dental caries, 25% had healthy teeth, and 1% presented other conditions. The counseling sessions were interactive and well received by students and teachers. In conclusion, the program successfully combined screening with education, providing immediate health benefits and fostering awareness for long-term oral health improvement